Improving Social Skills and Learning Outcomes with Carousel Feedback and Inside Outside Circle Modification Methods - Sulistyowati Sulistyowati; Siti Jubaidah (FITK UIN Walisongo Semarang, 2024)
This research aims to improve students' social skills and cognitive learning outcomes in sociology subjects by utilizing the modified Carousel Feedback and Inside Outside Circle methods. This research is classroom action research carried out in two learning cycles. Each cycle consists of planning stages, implementing actions, observing and reflecting. Research data was collected through observation, learning outcomes tests, interviews, questionnaires and documentation studies. The results of this study revealed significant improvements in several aspects. The implementation of learning by teachers increased by 11.25%, while the implementation of learning by students increased by 14.36%. In particular, there was a very striking increase in students' social skills, amounting to 43.54%, and students' cognitive learning outcomes in sociology subjects increased by 60.96%. The implication of this research is that the application of the modified Carousel Feedback and Inside Outside Circle methods can significantly improve students' social skills and cognitive learning outcomes in sociology subjects. This has an important impact because it helps students prepare to face future challenges. With consistent improvements in the implementation of teacher and student learning, as well as substantial improvements in social skills and cognitive learning outcomes, this model is worthy of application in a broader educational context to provide greater benefits for students.